Intermittent Hypoxia Enhances THP-1 Monocyte Adhesion and Chemotaxis and Promotes M1 Macrophage Polarization via RAGE. (8th October 2018) - Zhou, Jing; Bai, Wei; Liu, Qin; Cui, Jian; Zhang, Wei
Abstract : Intermittent hypoxia (IH) that resulted from obstructive sleep apnea (OSA) has been found to be a risk factor of coronary artery disease. IH and the receptor for advanced glycation end products (RAGE) expression are known to activate monocyte/macrophage and associated with atherosclerosis development, while their effects on monocyte adhesion, chemotaxis to the endothelium, and macrophage polarization remain unknown. In the present study, RAGE in THP-1 monocytes was inhibited by shRNA lentiviral particles, followed by exposure to IH. Cell adhesion assay, transwell migration assay, and macrophage polarization assays were performed to study the effects of IH and RAGE. The mRNA and protein expression levels were investigated by RT/real-time PCR and western blot analysis, respectively. We found that IH increased RAGE expression and activated NF-кB signalling in THP-1 monocytes. The results also revealed that IH enhanced the MCP-1-mediated THP-1 monocyte adhesion and chemotaxis and promoted macrophage polarization toward a proinflammatory phenotype, which was mediated by RAGE activity. Additionally, inhibition of chemokine receptor type 2 (CCR2) suppressed the IH-induced monocyte adhesion and chemotaxis. These results demonstrated a potential role of monocyte adhesion, chemotaxis, and macrophage polarization in the development cardiovascular diseases induced by IH and identified that RAGE could be a promising therapeutic target to prevent atherosclerosis in patients with OSA.